Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar - Grismer, L. Lee; Wood, Perry L. Jr.; Thura, Myint Kyaw; Win, Nay Myo; Quah, Evan S. H. (Zootaxa, 2019)
Two new species of Bent-toed Geckos of the Cyrtodactylus peguensis group are described from foothill areas occurring on opposite sides of the Ayeyarwady Basin. Cyrtodactylus nyinyikyawi sp. nov. from the Shwe Settaw Wildlife Sanctuary, Magway Region in the east and C. pyadalinensis sp. nov. from the Panluang-Pyadalin Wildlife Sanctuary, Shan State in the west bear unique suits of morphological and color pattern character states separating them from all species in the peguensis group. Additionally, a molecular phylogeny based on the mitochondrial gene ND2 indicates that neither species is nested within, nor sister to any known species in the group. This study augments recent and ongoing studies showing that the Ayeyarwady Basin is herpetologically more diverse than previously considered and should be incorporated into ongoing discussions concerning conservation efforts in Myanmar.